MODELING OF EVAPORATION LOSSES IN SEWAGE SLUDGE DRYING BED (Nigerian Journal of Technology, 2015)
A model for evaporation losses in sewage sludge drying bed was derived from first principles. This model was developed based on the reasoning that the rate at which evaporation is taking place is directly proportional to the instantaneous quantity of water in the sludge. The aim of this work was to develop a model to assist in the design of drying beds for effective treatment of wastes derived from households’ septic systems.  Data generated after evaporation experiment in sewage sludge drying bed over a period of 15 days at 24 hours intervals was used for the modeling. The model was calibrated and regressed using data for days 1 to 8 by employing the Pearson’s correlation coefficient, “ ” was found to be -0.96124, after which verification was done and regressed using data for days 9 to 15 and  was found to be 0.9969 that these fits validates the model. Materials balance show that evaporation reduces with increase in seepage losses which can be enhanced with use of conditioners and coarser sands because of their larger pore spaces. It was discovered that evaporation from the sludge follows first order kinetic in agreement with the fundamental concept. The model will help in the prediction of total water losses due to evaporation over a given period which would aid in the design of drying beds.  http://dx.doi.org/10.4314/njt.v34i4.31